2014
DOI: 10.4103/0975-7406.130955
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in mortality and teratogenicity following simultaneous administration of folic acid and vitamin E with antiepileptic, antihypertensive and anti-allergic drugs

Abstract: Aim:The present study was designed to evaluate the teratogenic effects on breeding pattern in mice following administration of lamotrigine (LT) and levetiracetam (LV) and its combination with anti-hypertensive and anti-allergic drugs. Moreover, possibility of decrease in teratogenic effect was also evaluated upon simultaneous administration of these combinations with folic acid or vitamin E.Materials and Methods:The study was carried out on mature female mice housed in polycarbonate breeding cages. Drugs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…The morphological and immunohistochemical features of the cystic lesion that was incidentally found adjacent to the salivary gland in the present goat supported a LEC diagnosis. Our observations were in line with previous human studies that reported LEC as an epithelial-lined cyst in a lymph node adjacent to or embedded in the major salivary gland [ 3 ]. Even though a cystic benign lymphoepithelial lesion has been more often found in the parotid glands in HIV-positive patients, there are some reports of a LEC of the submandibular gland also accompanying HIV infection [ 2 , 6 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The morphological and immunohistochemical features of the cystic lesion that was incidentally found adjacent to the salivary gland in the present goat supported a LEC diagnosis. Our observations were in line with previous human studies that reported LEC as an epithelial-lined cyst in a lymph node adjacent to or embedded in the major salivary gland [ 3 ]. Even though a cystic benign lymphoepithelial lesion has been more often found in the parotid glands in HIV-positive patients, there are some reports of a LEC of the submandibular gland also accompanying HIV infection [ 2 , 6 ].…”
Section: Discussionsupporting
confidence: 92%
“…The other theory suggests that reactive lymphoid proliferation occurs in the lymph nodes of the parotid gland or submandibular gland. The metaplasia in the salivary ducts is caused by the migration of HIV-infected cells, which indirectly leads to cyst formation [ 2 , 3 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that folic acid, L-carnitine, and zinc are often associated with other substances in order to achieve a synergic effect on infertility reduction in humans and animals [20][21][22][23]. The systemic administration of a combination of vitamin E and folic acid counteracted oxidative damage and apoptosis in the uterine cells of a streptozotocininduced rat model [24], while several studies revealed the protective effect of folic acid on teratogenesis [25][26][27]. L-Carnitine seemed to be effective in preventing meiotic oocyte damage, significantly reducing reactive species of oxygen and apoptosis in porcine oocytes [28].…”
mentioning
confidence: 99%